APLICAÇÃO DE REVESTIMENTOS COMESTÍVEIS EM ABACAXI MINIMAMENTE PROCESSADO - DINON, PATRÍCIA; TIECHER, ALINE; ROSSO, ANA C.; CORTE, DAIANE D.; SCHÖFFER, JÉSSIE D. N.; PEREIRA, MARCIELE H.; VICENZI, RAUL (Salão do Conhecimento, 2013)
Resumo